Polymorphism of Prolactin Gene and Its Association with Egg Production Trait in Four Commercial Chicken Lines - OSMAN, MOHAMED M.M.; HEMEDA, SHAABAN A.; HASSANIN, ABEER A.I.; HUSSEINY, WALAA A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Broodiness is a behavioral trait observed in most common breeds of domestic fowl and due to its fundamental role in avian reproduction, it has been of great interest to poultry scientists, breeders and producers of hatching eggs. Prolactin gene (PRL) is generally accepted as crucial to the onset and maintenance of broodiness in birds and thus plays a crucial role in egg production. Therefore, the present study aimed to screen the Single Nucleotides Polymorphisms (SNPs) of prolactin gene in four commercial chicken lines namely Hubbard F15, Lohmann, Cobb500, and Avian48 using PCR and direct sequencing. A total number of forty chickens (ten females from each of the four commercial chicken lines) were used. Blood samples were collected aseptically from brachial (wing) vein of the chickens for genomic DNA extraction. PCR reaction was done using five pairs of primers, one sense (F) and one antisense (R) primer for each of the five exons of prolactin gene. Finally, DNA sequencing and Single Nucleotide Polymorphisms (SNPs) analysis was done using Laser gene Megalign program. The results showed three SNPs in Hubbard F15 chicken line; one synonymous SNP at the position 3838 bp (ACC/ACT-transition) in exon 2 while in exon 5, two SNPs were detected; one non-synonymous single nucleotide polymorphism at the position 7921bp (CCT/TCT-transition) which results in amino acid changes at codon positions 169 (P/S), and one synonymous single nucleotide polymorphism at the position 8187 bp T/ C. The study concluded that this SNP in PRL gene could be used as the potential molecular markers for egg production traits in chicken.